Problematika Pembelajaran SKI Di MTs Salafiyah Syafiiyah Bandung Diwek Jombang - Mar'atul Azizah; Rina Bayu Winanda (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2021)
The subject of Islamic history is underestimated or is only considered a complementary subject by students. So that here the researcher is interested in researching about how the problems of learning Islamic Cultural History at MTs Salafiyah Syafiiyah Bandung Diwek Jombang and how the teacher's efforts in overcoming the problems of learning the History of Islamic Culture at MTs Salafiyah Syafiiyah Bandung Diwek Jombang. This research uses a qualitative approach. Data collection methods: observation, interviews and documentation. The data analysis technique used Miles and Huberman's interactive model which included data reduction, data presentation and conclusion drawing. To check the validity of the data, it was used research extension, observation persistence and triangulation. The results of this study found that: Mathematics of learning resource problems are incomplete, lack of understanding of the method, the lack of media so that it meets the learning objectives, student problems before and during learning, some evaluation scores are below standard. The teacher's efforts: learning resources are handled with the internet as a complementary source, methods are handled with other methods prepared by the teacher, media are overcome with other media that are easy to find, students are overcome with several common things, evaluation is overcome with remedial programs.